Overexpression of a beta‐1, 6‐glucanase gene GluM in transgenic rice confers high resistance to rice blast, sheath blight and false smut. Issue 6 (14th February 2023) - Shen, Enlong; Wang, Xingchao; Lu, Zhaoxi; Zhou, Fei; Ma, Weihua; Cui, Zhongli; Li, Zhoukun; Li, Changyan; Lin, Yongjun
Abstract: BACKGROUND: Frequent fungal diseases tend to lead to severe losses in rice production. As a main component of the fungal cell wall, glucan plays an important role in the growth and development of fungi. Glucanase can inhibit the growth of fungi by breaking glycosidic bonds, and may be a promising target for developing rice varieties with broad‐spectrum disease resistance. RESULTS: We transferred a codon‐optimized β‐1, 6‐glucanase gene ( GluM ) from myxobacteria into the japonica rice variety Zhonghua11 (ZH11), and obtained a large number of individual transgenic plants with GluM overexpression. Based on molecular analysis, three single‐copy homozygous lines with GluM overexpression were selected for assessment of fungal disease resistance at the T3 generation. Compared with that of the recipient cultivar ZH11, the area of rice blast lesion in transgenic rice was reduced by 82.71%; that of sheath blight lesion was decreased by 35.76%–43.67%; the sheath blight resistance in the field was enhanced by an average of 0.75 grade over 3 years; and the incidence of diseased panicles due to rice false smut was decreased by 65.79%. More importantly, there was no obvious loss of yield (without a significant effect on agronomic traits). Furthermore, plants overexpressing a β‐1, 6‐glucanase gene showed higher disease resistance than rice plants overexpressing a β‐1, 3‐glucanase gene derived from tobacco. CONCLUSION: The β‐1, 6‐glucanase gene GluM can confer broad‐spectrum disease resistance to rice, providing an environmentally friendly alternative way to effectively manage fungal pathogens in rice production. © 2023 Society of Chemical Industry. Abstract : Our study indicates that the β‐1, 6‐glucanase gene GluM can confer broad‐spectrum fungal disease resistance to rice, because of its ability to cleave β‐1, 6‐glycosidic bonds in the fungal cell wall.